Analisis Penggunaan Multiplatform Pada Pembelajaran Daring Sekolah Dasar di Kota Pontianak - Adha Maulana; Dessy Setyowati (Universitas Negeri Makassar, 2021)
This study aims to describe the use of multiplatform applications in online learning in elementary schools in Pontianak. This research used descriptive analysis with qualitative approach. The sample of this research is elementary school teachers using online learning in class. The data were collected using a questionnaire about the use of multiplatform applications in online learning in elementary schools in Pontianak City. The data were analyzed using qualitative descriptive. The results showed that the applications that are commonly used in online learning by teachers were Whatsapp, Google Classroom, and Zoom. Teaching by Whatsapp application had the highest percentage (84%). This is due to the limitations of teachers and students in using other multiplatform applications.